2017
DOI: 10.21037/cdt.2017.09.12
|View full text |Cite
|
Sign up to set email alerts
|

Statins as a preventative therapy for venous thromboembolism

Abstract: The anti-inflammatory effects of statins have likely not been used to their fullest extent, particularly in reducing venous thromboembolic events. Current therapy for thrombotic events hinges on anticoagulation via heparin, warfarin or new oral anticoagulants. Interventional procedures with thrombectomy may also play a critical role. Unfortunately, thrombotic events can occur and recur despite meticulous anticoagulation therapy. Venous thromboembolism (VTE) includes both deep vein thrombosis (DVT) and pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
0
16
0
2
Order By: Relevance
“…We found that patients with COVID-19 receiving statin therapy prior to admission are less likely to develop a PE. Statins have been previously described to be associated with decreased rates of venous thromboembolism, as well as decreased risk of recurrent PE ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients with COVID-19 receiving statin therapy prior to admission are less likely to develop a PE. Statins have been previously described to be associated with decreased rates of venous thromboembolism, as well as decreased risk of recurrent PE ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, statins have been proven to provide multiple effects, not just hypolipidemic effects. Statins can be used for venous thromboembolism, 22,23 cancers, 24 stroke, [25][26][27]31 and even as an antiarrhythmic drug. [28][29][30] However, statins have already been proven to reduce stroke risk and atherosclerosis mainly by reducing low-density lipoprotein cholesterol, which is exactly the effect of hypolipidemic agents and not by reducing inflammation.…”
mentioning
confidence: 99%
“…The concentration of fibrinogen and alterations in fibrin clot properties could also be mediated by statins, which are used in the management of hyperlipidemia. Statins are associated with the modulation of PAI-1 and tPA activity, influence fibrinogen concentration, and have an impact on fibrinolysis [29][30][31]. Statins could increase the permeability of clots and thus enhance fibrinolysis [30].…”
Section: Discussionmentioning
confidence: 99%